2020
DOI: 10.12944/carj.8.1.07
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of excess water tolerant rice varieties Swarna sub-1 and CR-1009 sub -1 under Head to Head Project in East and South- Eastern Coastal Plain zone of Odisha

Abstract: Flash flood or submergence is a common phenomenon in rice growing rainfed lowland areas that seriously affects crop establishment leading to severe yield losses. A few submergence–tolerant rice varieties have been developed by introgression SUB -1 gene into mega rice varieties of South Asia. Performance of this variety can be further enhanced through adoption of appropriate management practices. Farners Participatorty trials were conducted using Swarna- sub-1 and CR 1009 sub-1 during kharif, 2017 in three adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…This technology can be implemented on lines, new high-yielding, or local rice varieties with the Sub-1 gene. Dash et al [37] reported that the recommendation for cultivation technology for the Swarna-Sub-1 and CR 1009 Sub-1 varieties is application of N: P: K fertilizer at a dose of 80-40-40 kg ha -1 , setting the seedlings transplanting age to 30 days after planting, and application of N fertilizer at a rate of 20 kg ha -1 at seven days after receding of floodwater. The implementation of this cultivation technology can recover the impact of immersion so that the yield of the Swarna-Sub-1 variety reaches 5.523 t ha -1 .…”
Section: Performance Of Immersion Tolerant Rice Varieties In Several ...mentioning
confidence: 99%
“…This technology can be implemented on lines, new high-yielding, or local rice varieties with the Sub-1 gene. Dash et al [37] reported that the recommendation for cultivation technology for the Swarna-Sub-1 and CR 1009 Sub-1 varieties is application of N: P: K fertilizer at a dose of 80-40-40 kg ha -1 , setting the seedlings transplanting age to 30 days after planting, and application of N fertilizer at a rate of 20 kg ha -1 at seven days after receding of floodwater. The implementation of this cultivation technology can recover the impact of immersion so that the yield of the Swarna-Sub-1 variety reaches 5.523 t ha -1 .…”
Section: Performance Of Immersion Tolerant Rice Varieties In Several ...mentioning
confidence: 99%
“…These results have been confirmed by multiple tests of submergence tolerance carried out in farmers' fields and greenhouses [7], and the same result has been observed in floodprone places [8] for the Swarna sub 1 variety. According to [9], introducing this variety will significantly increase rice yield in low-lying places.…”
Section: Ntroductionmentioning
confidence: 99%
“…Furthermore, a wide scale adoption of SS1, prior to floods would have resulted in an approximate increase in rice production by 26% [21]. Apart from flood tolerance, the SS1 seeds also reduce the risk of yield loss during the normal growing period i.e., when there is no flood impact [20,22,23]. Overall, the development of submergence-tolerant varieties allows farming communities to become more resilient to existing and growing flooding risks [24].…”
Section: Extent and Impact Of Flooding On Rice Productionmentioning
confidence: 99%